All-optical density downramp injection in electron-driven plasma wakefield accelerators - D. Ullmann; P. Scherkl; A. Knetsch; T. Heinemann; A. Sutherland; A. F. Habib; O. S. Karger; A. Beaton; G. G. Manahan; A. Deng; G. Andonian; M. D. Litos; et al. (Physical Review Research, 2021)
The properties of electron beams obtainable from plasma wakefield accelerators are largely determined by their injection into the plasma wave. Density downramps can facilitate injection of plasma electrons and are realized routinely in laser wakefield accelerators by gas-dynamic production of longitudinal downramp profiles. We show that density downramp injection is in fact a multidimensional process when operated below the spatiotemporal scales of the plasma wave. In beam-driven plasma waves, unlocking this interaction regime by microscopic plasma torches allows the generation of unique electron beams, such as planar counteroscillating twin beamlets. Our findings generalize density downramp injection and extend its capabilities, which may find applications ranging from radiation production to high-energy-physics research.